Answer:
n = (-4)
Step-by-step explanation:
Firstly expand the bracket
;2[3(1 - n) -2(1+n)]
;2[ 3 - 3n - 2 - 2n ]
;2[ -5n + 1 ]
; -10n + 2
then go back to the question and substitute the bracket with the simplified form above,
; 7n - 10n + 2 = 14
; -3n = 14 - 2
; -3n = 12...then divide both sides by (-3)
;Hence... n = (-4)
Have you tried doing (3x+18)+(9x-27)=99
Answer:
-2
Step-by-step explanation:
You make x= -3 then you insert it into the problem which is x= 2(-3)+4
2 times -3 is -6 which then you would get
-6+4 which equals -2
Answer:
3.1415926535 8979323846
Step-by-step explanation:
Answer:
Sam is 6, Destiny is 17
Step-by-step explanation:
(2xS)+5=D
D+S=23